National Standards: A Parent’s Perspective - Bill Courtney (New Zealand Journal of Teachers' Work)
Do parents strongly support National Standards? Or, more to the point, how many parents really understand it? Teachers must provide the judgments of students’ progress and achievement against the Standards and parents want to know how their children are doing at school, so they can support their learning. But if the Standards are not clear enough for teachers to be confident about them, or they have been set at the wrong level, then parents will lack the confidence to use the information contained in the reports. The issue with National Standards is not about the lofty, well-intentioned goals, but rather that the method chosen needs careful consideration before full-scale implementation is seriously considered.